2023
DOI: 10.3389/fcvm.2023.1126590
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between myocardial work indices and liver function classification in patients with hepatitis B cirrhosis: A study with non-invasive left ventricular pressure-strain loop

Abstract: BackgroundLiver cirrhosis is closely associated with cardiac dysfunction. The aims of this study were to evaluate left ventricular systolic function in patients with hepatitis B cirrhosis by non-invasive left ventricular pressure-strain loop (LVPSL) technique, and to explore the correlation between myocardial work indices and liver function classification.MethodsAccording to the Child-Pugh classification, 90 patients with hepatitis B cirrhosis were further divided into three groups: Child-Pugh A group (n = 32)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Studies published later, when guidelines for GLS measurement were more standardized, yielded varying results. Most studies did not find statistically significant differences between patients and controls [38,40,41], while some studies found lower absolute values for patients with cirrhosis than for controls [37,42]. Some studies even found increased GLS values in cirrhotic patients compared to controls.…”
Section: How Different Are Left Ventricular Strain Values Of Cirrhoti...mentioning
confidence: 99%
“…Studies published later, when guidelines for GLS measurement were more standardized, yielded varying results. Most studies did not find statistically significant differences between patients and controls [38,40,41], while some studies found lower absolute values for patients with cirrhosis than for controls [37,42]. Some studies even found increased GLS values in cirrhotic patients compared to controls.…”
Section: How Different Are Left Ventricular Strain Values Of Cirrhoti...mentioning
confidence: 99%